1983
DOI: 10.1250/ast.4.73
|View full text |Cite
|
Sign up to set email alerts
|

Perceived principal pitch of vibrato tones.

Abstract: lated by simple circuits that are easy to design when vibrato sounds are required. First, the analysis of performed musical sounds in order to define the location of principal pitch of vibrato sounds was attempted. But, a definite answer has not been obtained from this approach. As Shonle and Horan2) state, the results of various experiments have variously indicated that principal pitch is localized in the higher side of the extent of vibrato,3) another in the middle,4) and yet another in the lower side.5) Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Because of the necessity of stimulus control in experimental studies of perception, until recently previous research has used electronic or synthesized sound sources in place of acoustical instruments. These studies have indicated that perceived pitch corresponds closely to the mean of the frequency-modulated sound (Iwamiya, Kosugi, & Kitamura, 1983;Seashore, 1938;Shonle & Horan, 1980;van Besouw, Brereton, & Howard, 2008). Shonle and Horan extended the range of modulations to whole tones, and found that perceived pitch of those wider modulations corresponded more closely to the geometric mean of the extreme frequencies, a frequency only slightly lower than the arithmetic mean.…”
mentioning
confidence: 97%
“…Because of the necessity of stimulus control in experimental studies of perception, until recently previous research has used electronic or synthesized sound sources in place of acoustical instruments. These studies have indicated that perceived pitch corresponds closely to the mean of the frequency-modulated sound (Iwamiya, Kosugi, & Kitamura, 1983;Seashore, 1938;Shonle & Horan, 1980;van Besouw, Brereton, & Howard, 2008). Shonle and Horan extended the range of modulations to whole tones, and found that perceived pitch of those wider modulations corresponded more closely to the geometric mean of the extreme frequencies, a frequency only slightly lower than the arithmetic mean.…”
mentioning
confidence: 97%
“…Because of the necessity of stimulus control in experimental studies of perception, most all previous research has used electronic or synthesized sound sources in place of acoustical instruments. Most of these studies show that perceived pitch corresponds closely to the mean of the frequency-modulated sound (Iwamiya, Kosugi, & Kitamura, 1983;Seashore, 1938;Shonle & Horan, 1980). Shonle and Horan found that perceived pitch of wider (whole-tone) modulations corresponded more closely to the geometric mean of the extreme frequencies, a frequency only slightly lower than the arithmetic mean.…”
Section: Listeners' Perception Of Pitch Center During Vibratomentioning
confidence: 99%
“…Can the concept of overall loudness of level‐fluctuating sounds exist? In the case of the pitch of a vibrato tone (tone with frequency modulation), the principal pitch is determined by the carrier frequency (Iwamiya, Kosugi, & Kitamura, 1983). Listeners can detect rapid frequency changes over time and also judge the principal pitch as a representative value of the vibrato tone.…”
Section: Possible Representative Values For the Variation And Generatmentioning
confidence: 99%